2003
DOI: 10.1034/j.1600-0412.2003.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Fear of childbirth: a neglected dilemma

Abstract: Severe fear of childbirth complicates 6% to 10% of parturients and is manifested as nightmares, physical complaints and difficulties in concentrating on work or on family activities. Very often fear of childbirth leads to request for an elective cesarean section (CS). In Finland, Sweden, and the United Kingdom, fear of childbirth or maternal request is the reason for about 7-22% of CS births. Fear of childbirth is as common in nulliparous as in parous women. Fear of labor pain is strongly associated with the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
168
3
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(193 citation statements)
references
References 94 publications
11
168
3
11
Order By: Relevance
“…Based on their results, 31.1% of Swedish pregnant women and 29.5% of Australian pregnant women suffered from severe fear related to childbirth. The rate of severe fear in the present study is higher than what has been reported in developed countries which may be due to difference in culture, attitude, and perception of pregnant women, different instruments, time of measurement, quality of prenatal care, and education (Haines et al, 2012;Haines et al, 2011;Saisto & Halmesmäki, 2003;Weaver et al, 2007). Despite availability of prenatal care for all women in Iran, childbirth education programs are lacking in the Iranian prenatal care system.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Based on their results, 31.1% of Swedish pregnant women and 29.5% of Australian pregnant women suffered from severe fear related to childbirth. The rate of severe fear in the present study is higher than what has been reported in developed countries which may be due to difference in culture, attitude, and perception of pregnant women, different instruments, time of measurement, quality of prenatal care, and education (Haines et al, 2012;Haines et al, 2011;Saisto & Halmesmäki, 2003;Weaver et al, 2007). Despite availability of prenatal care for all women in Iran, childbirth education programs are lacking in the Iranian prenatal care system.…”
Section: Discussioncontrasting
confidence: 54%
“…Melender (2002) reported that pregnant women experience a variety of fears about the baby's well-being, which manifest as symptoms of stress. Lack of social support, low self esteem, high level of daily stressors and dissatisfaction of marital relationship are predisposing factors of fear related to pregnancy (Saisto & Halmesmäki, 2003). Social and psychosocial aspects of the woman's life, self esteem, social support and quality of marital relationship, as well as a negative experience of labour and delivery are associated with the fear related to childbirth.…”
mentioning
confidence: 99%
“…Severe fear of childbirth affects around 6-10% of women worldwide (Saisto & Halmesmäki, 2003). A study in Australia on 1410 women showed that the prevalence of fear of childbirth was 24% and 31.5% of nulliparous women had severe fear of childbirth (Toohil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It influences daily life activities, the decision on a cesarean section delivery, and sometimes even the postponement of pregnancy (Melender, 2002;Hildingsson, Rådestad, Rubertsson & Waldenstrom, 2002;Bahl, Strachan & Murphy, 2004;Nilsson & Lundgren, 2009). During childbirth, fear leads to an increased perception of pain (Lang, Sorrell, Rodgers & Lebeck, 2006), potentially causing the woman to request an elective caesarean section (Saisto, Salmela-Aro, Nurmi, & Halmesmäki, 2001;Hildingsson et al, 2002;Saisto, & Halmesmäki. 2003;Bahl et al, 2004), prolong labour, and contribute to a negative birth experience and low satisfaction levels with childbirth (Larsen, O'Hara, Brewer, & Wenzel, 2001;Hildingsson et al, 2002;Johnson, & Slade 2002;Melender, 2002;Hofberg, & Ward, 2003;Saisto, & Halmesmäki, 2003;Wax Cartin, Pinette, & Blackstone, 2004;Waldenstrom, Lang et al, 2006;Hildingsson, 2008;Rouhe, Salmela-Aro, Halmesmäki, & Saisto, 2008;Nilsson & Lundgren, 2009;Fenwick, Gamble, Nathan, Bayes, & Hauck, 2009).…”
mentioning
confidence: 99%